Effect of feeding formaldehyde-treated mustard-cake supplemented with urea treated wheat-straw on rumen metabolism in buffalo - MADAN, JYOTSANA; PURI, J P (The Indian Journal of Animal Sciences, 2013)
Three rumen fistulated, male buffaloes, 2-2.5 years old weighing about 250 kg were fed wheat straw + concentrate mixture (mustard-cake 30 parts, maize 30 parts, barley 20 parts, oats 17 parts, mineral mixture 2 parts and salt 1 part) group A (control); wheat straw + concentrate mixture having mustard cake treated with formaldehyde @ 2g/·1 OOg CP (group B); and basal diet as in group B supplemented with urea treated (4% urea + 40% moisture, ensiled for one month) wheat straw (group C). The concentration of total nitrogen, ammonia nitrogen, TCA-ppt. nitrogen and pH of rumina I fluid decreased significantly (P<0.0 1) in group B, but increased significantly (P<0.01) in group C. The mean values of total volatile fatty acids (TVF A) concentration in rumen liquor were 101.35 ± 3.012; 101.97 ± 2.90 and 123.08 ± 3.012 meq/l in groups A,B and C respectively. The molar percentage of acetic acid increased significantly (P<0.01) in group B but decreased significnalty (P<0.01)in group C, whereas the reverse trend was observed with propionic acid. The concentration of butyric acid was not affected in group B, but increased significantly (P<0.01) in group C. The results indicated that feeding of urea treated straw with protected protein supplementation is beneficial for ruminants.